Pelatihan Pembuatan Sabun Mandi Padat dari Minyak Kelapa, Minyak sawit Dan ekstrak Biji Melinjo Di Desa Pardomuan Tapanuli Selatan: Pelatihan Pembuatan Sabun Mandi Padat dari Minyak Kelapa, Minyak sawit Dan ekstrak Biji Melinjo Di Desa Pardomuan Tapanuli Selatan - Elmi Sariani, Hasibuan; Yulia Vera; Dini Mayasari; Afrinadewi Lubis; Mutia Sari Lubis (Universitas Aufa Royhan Di Kota Padangsidipuan, 2025)
Soap is a preparation obtained from a mixture of fatty acids and strong bases used to clean dirt that sticks. Soap is part of the form of pharmaceutical preparations which are cosmetics used as body cleansers and also as non-natural protectors on the skin. The purpose of this community service is to develop public knowledge about making soap and the uses of soap. The basic ingredients for making this solid soap are coconut oil and palm oil. While melinjo seed extract is used as an anti-bacterial for soap. While NaOH is used as an alkali. From the results of community service, it is known that the community is very enthusiastic about the making of solid soap from coconut oil, palm oil and melinjo seed extract because the community can find out how to make solid soap and also the benefits of solid soap. Conclusion The community knows how to make soap and also the benefits of the soap that has been made.